Local government and administration in Bangladesh the state of the art - Aminuzzaman, Salahuddin (Philippine Journal of Public Administration, 1993)
In the last three decades, Bangladesh has witnessed a series of experimentation in institution-building at the local level. All the ruling political regimes attempted to develop institutions at the local level to have apolitical and power base at the grassroots. However, none of the attempts could bring about any significant and positive change in the quality of life of the people in the local areas. An overview of the growth and evolution of local government bodies in Bangladesh indicates that these had all along been under the administrative control of the public bureaucracy on one hand and under the extreme political control of the national government on the other. The local bodies hardly enjoyed any kind of functional as well as political autonomy. The national government never followed a consistent policy towards shaping the institutional makeup of the local bodies. Local bodies are found to be weak in terms of their respective tax and other resource base. The personnel system of the local bodies is also not appropriately designed. As a result, the local bodies could neither become politically viable nor could gain any credibility from the local people. In fact, local government bodies in Bangladesh under. the given legal framework is neither a "self-governing" body nor a viable form of "government." These could simply be branded as extensions of the national government with limited scope of local participation.